Current Assets Exercises III - eBooks and textbooks from bookboon.com - Walther, Larry M. (bookboon.com, 2016)
This exercise book is the third of four exercise books that correspond directly with the Current Assets textbook. The exercises relate specifically to Part 3 of the Current Assets textbook. Students will work exercises related to Accounts Receivable and Notes Receivable. Exercises credit sales, accounting for uncollectible accounts, direct write-off versus using the allowance method, notes receivable, and adjusting entries.